The Roles of Language Shift in English Language Teaching (A Case Study in the Class of Grammar III in the English Department in Universitas Galuh Ciamis) - Febriani, R Bunga (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2017)
This study emphasizes the use of language shift in the English language teaching classroom. Language shift is a common phenomenon in multilingual conversations, in this case, in the teaching and learning process in language classrooms. The purposes of the study are to find out the use and the roles of language shift in EFL classrooms, how the roles contributed to the Teaching English as Foreign Language in the EFL, and how the language shift affects the process of teaching and in the EFL classroom. The study employed a qualitative approach by using interview and classroom observations as the instruments of the research. The study was a case study in the teaching and learning process of Grammar III to the second-grade students of English department in Universitas Galuh Ciamis. The findings of the study revealed that using language shift while learning and teaching English is useful in the process of teaching and learning English as a foreign language, in this case in the subject of Grammar III subject; and that code-switching as one of the kinds of language shift is necessary and inevitable in language classrooms.